(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article covers the issues of providing students with a unified scientific view of the universe in general secondary schools. Natural sciences physics, chemistry, biology, geography were considered together and a single scientific view of the universe was interpreted.